2012
DOI: 10.1002/ajmg.a.35290
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune disease and multiple autoantibodies in 42 patients with RASopathies

Abstract: The association of RASopathies [Noonan syndrome (NS) and Noonan-related syndromes] and autoimmune disorders has been reported sporadically. However, a concomitant evaluation of autoimmune diseases and an assessment of multiple autoantibodies in a large population of patients with molecularly confirmed RASopathy have not been performed. The clinical and laboratory features were analyzed in 42 RASopathy patients, the majority of whom had NS and five individuals had Noonan-related disorders. The following autoant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 32 publications
3
66
0
1
Order By: Relevance
“…64 Because autoimmune thyroiditis is common in the general population, measurements of thyroid function are recommended at diagnosis. Only a few instances of hypothyroidism have been documented in CFC, 29 so follow-up thyroid testing can be decided by an endocrinologist.…”
Section: State-of-the-art Review Article Endocrine Issuesmentioning
confidence: 99%
“…64 Because autoimmune thyroiditis is common in the general population, measurements of thyroid function are recommended at diagnosis. Only a few instances of hypothyroidism have been documented in CFC, 29 so follow-up thyroid testing can be decided by an endocrinologist.…”
Section: State-of-the-art Review Article Endocrine Issuesmentioning
confidence: 99%
“…In a series of 42 patients with RASopathies, 52% were shown to have autoantibodies against various tissues. 23 Other investigators suggested a predisposition to the development of systemic lupus erythematosus in NS. 24 …”
Section: Ras and The Ras/mitogen-activated Protein Kinase Signaling Cmentioning
confidence: 99%
“…Additionally, increased serum level of mtDNA was detected in patients diagnosed with various neurodegenerative disorders, such as autism, Parkinson disease and multiple sclerosis [10,11,12]. Several authors have suggested that mtDNA can act as trigger points for the development of autoimmune disorders as well [10,13]. Although immune reactivity towards nucleic acids is well established, it remains to determine which type of nucleic acids are more immunogenic in SLE.…”
Section: Introductionmentioning
confidence: 99%